Nanostructured Oxide Thin Films for Sustainable Development - Mele P.; Singh S.J.; Saini S.; Jha A.K.; Adam M.I. (Elsevier Ltd, 2023)
Conversion efficiency; Deposition; Energy conversion; Energy efficiency; Films; Fossil fuels; Oxide films; Oxides; Phonon scattering; Pulsed laser deposition; Structures (built objects); Superconducting films; Superconducting materials; Thermoelectric energy conversion; Artificial pinning centers; Experimental conditions; Nanodefects; Nanostructured thin film; Structure and morphology; Superconducting properties; Thermoelectric properties; Thermoelectrics; Thin films